Splices: when science catches up with science fiction - Pusch, Anne Franciska (Nanoethics, 2015)
This paper examines human-nonhuman splices from a multidisciplinary approach, involving bioengineering and literary studies. Splices are hybrid beings, created through gene-splicing—a process which combines the DNA of the two species, resulting in a hybrid or chimeric being. A current trend in biotechnological research is the use of spliced pigs for xenotransplantation. Hiromitsu Nakauchi’s pancreas study that splices pigs with human iPS [induced pluripotent stem] cells in order to grow human organs inside pigs is being compared to a highly similar case of porcine hybrids: the pigoon from Margaret Atwood’s fictional MaddAddam trilogy. Atwood’s pigoons are pigs, genetically modified with human stem cells to facilitate the growth of various human organs for use in organ transplants with no risk of rejection. The case studies from science and science fiction overlap significantly and thus allow for a critical reading of the two highly different sources with a focus on ethical and moral questions regarding the use and abuse of nonhuman animals for human purposes. Furthermore, the context of the fictional works adds new layers of knowledge and new perspectives to the problematic issue of animal “enhancement.” Through the dynamic agency that can be detected within Atwood’s novels and that encompasses human, animal, and hybrid agency, the reader can develop empathy for other-than-human experiences and use this new perspective for a critical reflection of actual technoscientific developments that affect both human and nonhuman animal life. The combination of the two discourses reveals a value of science fiction for both the scientific community and society at large, demonstrating how its critical reception can result in enhanced ethical standards.